Calculating the 'greening' effect: A case study approach to predict the gross margin losses in different farm types in Germany due to the reform of the CAP - Barbara Heinrich (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2012)
Agricultural policy is designed to achieve certain goals. One goal that is of increasing importance in public discussion is 'public money for public goods' i.e. the compensation for the provision of public goods and the internalization of externalities. The European Union's Common Agricultural Policy is currently undergoing a reform process which inter alia aims to achieve a higher environmental standard in agricultural production by binding direct payments to practices beneficial for the climate and the environment (the so-called 'greening'). I simulate how farms would respond to these measures using a case study farm modeling approach and data for different farm types in Germany. I find that the considered and currently envisaged 'greening' measures can be expected to function in general due to the linkage to the direct payments, which provide a strong disincentive to forego participation. The individual economic outcome strongly depends on the current intensity of the farm in question and on the implementation details of the introduced measures. However, farms with very high gross margins per hectare will forego the support scheme.
Keywords: 330; greening; Common Agricultural Policy; reform of the CAP; agri-environmental measures; direct payments